Interpretation of Power Politics in Educational Curriculum Policy: Systematic Literature Review - Jaya, Christian Arief; Simanungkalit, Indra; Simanungkalit, Vista Gustina (Edukasiana: Jurnal Inovasi Pendidikan, 2025)
Power politics is defined as a form of effort to maintain and legalize in various ways to achieve specific goals. It has a strong influence on policy decision-making and the formation of laws. Power politics also influences education, determining education policies that underlie changes in the education curriculum. This research aims to explain the influence of power politics in education policy and the influence of power politics in changing the 2013 curriculum to the Merdeka curriculum (2013 - present). The approach used in this research is a literature study using the systematic literature review (SLR) method, which refers to the PRISMA protocol. Data and data sources were obtained from databases such as Semantic Scholar, Garuda, and Research as well as books from the Education Technology library and the Rumah Ilmu Unnes Library. The results of this research show that power politics influences educational policies, and this also influences curriculum determination (curriculum changes), as happened in the 2013 curriculum and the independent curriculum.